Short-term Assessment of Phytoplankton Composition and Abundance in Cebu and Subic Bay Ports, Philippines - Austero, Nero M.; Azanza, Rhodora V. (Science Diliman: A Journal of Pure and Applied Sciences, 2018)
A short-term study to evaluate the composition and abundance of marine diatoms and dinoflagellates in two major ports in the country was conducted in May 2015 and July 2015. Pseudo-nitszchia spp. bloom comprising about 42.3% of the total phytoplankton population was observed in Cebu International Port in May 2015. Furthermore, Chaetoceros spp. comprised about 53.58% of the total phytoplankton population in Naval Supply Depot (NSD) terminal in May 2015, while Thalassionema spp. and Leptocylindrus spp. accounted for 50.16% and 34.78%, respectively, of the total phytoplankton population in July 2015. Bloom-forming and potentially harmful species including diatoms, such as Coscinodiscus spp. , Nitzschia spp. , and Pseudo-nitzschia spp. , and dinoflagellates, such as Ceratium spp. , Ceratium furca, Gonyaulax spp. , Gymnodinium spp. , Linguludinium spp. , Phalacroma spp. , Prorocentrum micans, Prorocentrum spp., and the IOC-UNESCO listed Harmful Algal Bloom (HAB) species Dinophysis caudate , were also recorded. The results of this study contribute to the establishment of baseline data for phytoplankton composition and abundance, which are necessary for the identif ication of potentially toxic/harmful microalgae which pose risks of ballast water inclusion and transport. Keywords: Phytoplankton, ports, harmful algal blooms, diatoms, dinoflagellates